Daya Dukung Fondasi Dangkal dan Dalam Gudang Air Minum dalam Kemasan (AMDK) Kota Malang - Arif Wahono; Fx. Hevie Dwi Novianto; Adi Setio (Jurnal Talenta Sipil, 2026)
Foundation design plays a crucial role in ensuring structural stability and safety, particularly for industrial buildings constructed on cohesive soils. Soil characteristics significantly influence the selection of foundation types and their bearing capacities; therefore, an evaluation of both shallow and deep foundations under the same soil conditions is required. This study aims to determine the bearing capacity of shallow foundations using Standard Penetration Test (SPT) data, evaluate the bearing capacity of deep foundations based on Cone Penetration Test (CPT) data, and analyze the effect of foundation dimension variations for the planned Bottled Drinking Water (AMDK) warehouse in Malang City. The study employed a quantitative descriptive approach using secondary data obtained from geotechnical investigations and laboratory testing. The bearing capacity of shallow foundations was analyzed using the Terzaghi method, while the bearing capacity of deep foundations was calculated using an empirical approach based on CPT data. The results indicate that the bearing capacity of shallow foundations at a depth of 5 m ranges from 15.1 to 32.1 t/m² for strip foundations, 19.1 to 37.0 t/m² for circular foundations, and 19.1 to 37.4 t/m² for square foundations. Meanwhile, the bearing capacity of deep foundations at a depth of 10 m ranges from 399.07 to 1,617.29 tons, depending on the pile diameter used. The findings demonstrate that the Terzaghi method remains a relevant preliminary approach for evaluating foundation bearing capacity in relatively homogeneous cohesive soils. These results may serve as an initial reference for selecting alternative foundation systems; however, further verification is still required during the detailed planning and design stages.